FROM BUDGET TO BREAKTHROUGH: THE CRITICAL ROLE OF GOVERNMENT SPENDING IN PUBLIC WELFARE - Putri Dinarti, Riska; Silvia Damayanti; Muhammad Syahrul Maulana; Rizki Himawan Saputra; I Made Suparta, (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Public economics emphasizes the government's crucial role in resource management to promote social welfare. This article explores how government spending, particularly in the social protection sector, influences poverty reduction and inequality in Indonesia. By using secondary data from official sources and scholarly journals, the study finds that social protection spending positively impacts public purchasing power and economic stability. However, implementation challenges—such as targeting accuracy and inter-agency coordination—remain significant obstacles. Therefore, systemic improvements in the design and implementation of social protection programs are necessary for long-term impact.